2016
DOI: 10.1007/s12011-016-0787-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Choline on the Composition and Degradation Enzyme of Extracellular Matrix of Mice Chondrocytes Exposed to Fluoride

Abstract: Choline has been shown to mediate damage of the chondrocyte matrix and degradation enzymes of mice exposed to fluoride (F). To test the action of choline, pregnant mice were treated with differing amounts of F and choline. Newborn mice were weaned at 21 days after birth and treated with the same doses of F and choline as they mothers for 12 weeks. Using hematoxylin-eosin (HE) staining, real-time PCR (RT-PCR), and western blotting, changes in the structure of the cartilage, the expression of mRNA and protein re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In the present study, according to environmental levels, the mice in three NaF-treated groups were exposed to distilled water containing 25, 50, and 100 mg/L NaF corresponding to 11.3, 22.6, and 45.2 mg/L fluorine ion. The establishment of fluorosis model was also based on the previous reports from our laboratory. , EAO can be induced by three immunizations with syngeneic testicular homogenate emulsified with CFA at 14 d intervals in animals (rats and mice). , Some reports consider that chronic and excess F exposure can lead to its bioaccumulation in bones. , Even some investigations demonstrate that bone F concentration is an appropriate biomarker of chronic environmental fluoride exposure . The excessive uptake of F can affect the growth and development of animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, according to environmental levels, the mice in three NaF-treated groups were exposed to distilled water containing 25, 50, and 100 mg/L NaF corresponding to 11.3, 22.6, and 45.2 mg/L fluorine ion. The establishment of fluorosis model was also based on the previous reports from our laboratory. , EAO can be induced by three immunizations with syngeneic testicular homogenate emulsified with CFA at 14 d intervals in animals (rats and mice). , Some reports consider that chronic and excess F exposure can lead to its bioaccumulation in bones. , Even some investigations demonstrate that bone F concentration is an appropriate biomarker of chronic environmental fluoride exposure . The excessive uptake of F can affect the growth and development of animals.…”
Section: Discussionmentioning
confidence: 99%
“…Foodstuffs and groundwater are the main intake source of fluoride (F) . Most of the literature has demonstrated that F in low dose contributes to the growth and development of dental and bone in human and animal models, but chronic excessive intake of F could damage various tissues and organs, including the reproductive organs. , Reproductive health is one of the key factors for sustainable development of humans and animals. The testis, an important male reproductive organ, is the place of spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study also revealed that fluoride had a dose-response effect on bone morphogenetic proteins in fluorosis rats, and fluoride induced hypomethylation of specific CpGs ( 12 ). Zhao et al ( 15 ) reported that choline inhibited fluoride toxicity in the chondrocyte of rats and reduced the amount of fluoride in the organ tissues. In this regard, choline may play a methyl donor role against bone damage caused by excessive amounts of fluorine.…”
Section: Discussion Main Findingsmentioning
confidence: 99%
“…DNA methylation is determined by the availability of methyl groups from S-adenosylmethionine (SAM) ( 13 ), and is indirectly related to one-carbon metabolism nutrients, such as betaine, choline, methionine, folate, vitamin B 6 , and vitamin B 12 ( 14 ). Animal studies found that choline and methionine attenuated fluoride toxicity ( 15 , 16 ). These studies indicated that one-carbon metabolism nutrients may play a crucial role in preventing the fluorosis due to their involvement in the one-carbon metabolism pathway and their roles as methyl donors.…”
Section: Introductionmentioning
confidence: 99%
“…Methionine in combination with Vitamin E has been shown to be efficacious in skeletal fluorosis. While choline has been shown to induce a protective effect against fluoride in animal studies (Zhao et al, 2017), taurine is thought to restore renal function after fluoride exposure (Adedara et al, 2017). In addition, Punica granatum juice has been shown to mitigate the oxidative stress in rats (Bouasla et al, 2016) and Cistanche is thought to alleviate symptoms of fluorosis.…”
Section: Treatment Options and Modalities For Fluorosismentioning
confidence: 99%